R-CHOP intensification with mid-cycle methotrexate and consolidating AraC/TT with BCNU/aHSCT in primary aggressive lymphoma with CNS involvement - Steinhardt, Maximilian J.; Krummenast, Franziska C.; Rosenwald, Andreas; Gerhard-Hartmann, Elena; Heidemeier, Anke; Einsele, Hermann; Topp, Max S.; Duell, Johannes (Journal of Cancer Research and Clinical Oncology, 2022)
Purpose: Patients suffering from aggressive systemic peripheral lymphoma with primary central nervous system involvement (PCL) are a rare and sparsely investigated population. Recommended treatment regimens include a combination of intrathecal and systemic chemotherapy as well as whole brain radiotherapy while offering relatively poor survival. Methods: We conducted a single-center retrospective study that analyzed safety and outcome of 4 + 4 cycles Rituximab (R)-CHOP and R-high-dose Methotrexate (HD-MTX) for newly diagnosed, transplant-eligible patients (“Ping-Pong”), followed by Cytarabine (AraC)/Thiotepa (TT), BCNU/TT, and autologous hematologic stem cell transplantation (aHSCT). We retrospectively analyzed a set of 16 patients with high–intermediate or high-risk IPI status. Results: Overall response rate to Ping-Pong was 100% measured by CT/MRI, including 93.75% complete remissions after BCNU/TT followed by PBSCT. One patient failed to qualify for high-dose chemotherapy due to progression when receiving Cytarabine/TT. All patients experienced grade III adverse events, 3 of them a grade IV adverse event. Estimated progression-free survival is 93.75% after a 4.8-year follow-up currently. Conclusion: Our study suggests high effectivity of R-CHOP with mid-cycle MTX with aHSCT consolidation towards acceptable OS results in this challenging patient population.
CRIS-Team Scopus Importer:2023-03-23
Keywords: HD; Lymphoma; MTX; R-CHOP